Evaluación de la adición del 15%, 20% y 25% de harina de residuos de maracuya (Passiflora edulis) en la alimentación de cuyes (Cavia porcellus) en la etapa reproductiva en el barrio La Delicia, parroquia de Panzaleo, cantón Salcedo - Flores Quilismal, Jhon Henry (2015)
This research was conducted in La Delicia neighborhood, located in Panzaleo parish, Salcedo canton, Cotopaxi province, for a period of six months in the development of the entire thesis. The objective of the research was to evaluate the addition of three levels of residues of passion fruit (15%, 20% and 25%) in the feeding of guinea pigs in the reproductive stage. 40 female guinea pigs of 90-day-old were selected. 4 groups of 10 animals were selected randomly. The treatments were: T1 (balanced with passion fruit waste flour 15% plus forage), T2 (balanced with passion fruit waste flour 20% plus forage), T3 (balanced with passion fruit waste flour 25% plus forage) and T4 - control group (balanced without waste of passion fruit flour plus forage).The food ration provided according to the schedule was of 40 g of balanced per animal per day and 400 gr of feed per animal per day. In the same water ad libitum was supplied every day....